Food contribution to total daily energy intake in the Mexican population older than five years - Claudia Gabriela García-Chávez; Eric Monterrubio-Flores; Claudia Ivonne Ramírez-Silva; Tania C Aburto; Lilia S Pedraza; Juan Rivera-Dommarco (Instituto Nacional de Salud Pública, 2020)
Objetive. To identifiy the energy contribution (EC) of the food consumed in those older than five years and by sociodemographic characteristics in Mexican population. Materials and methods. We analyzed data from 24-hour recalls from 7 983 subjects ≥5 years included in the Encuesta Nacional de Salud y Nutrición 2012 (Ensanut 2012). The EC to total daily energy intake of 50 foods allocated to eight food groups at national level and stratified by age, area of residence, region and socioeconomic level was estimated. Results. Seven foods contributed 50% of total energy intake: tortilla and corn products (20.6%), sweet bread (6.6%), vegetable oils (4.9%), white bread and wheat products (4.9%), carbonated sugary drinks (4.6%), red meat (4.0%) and whole milk (4.0%). Other foods, which its consumption is recommended to increase due to its positive effects on health, showed minor contributions (less than 1.0%), with the exception of beans (3.3%). Great heterogeneity in intakes was observed between subgroups of the population. Conclusions. The identification of individual foods and their EC for both, food groups whose consumption should be increased as well as those that should be reduced can be useful for the design of regulatory actions and educational strategies aimed at reducing the diet related burden of disease.